SPECIFIC ASPECTS OF PLOWING PERIODS AND PLOWING DEPTH - Rajabova, Mahliyo Mahmudovna; Choriyev, Ravshan Sobirjon o‘g‘li; Azimova , Go‘zal Adizovna (Educational Research in Universal Sciences, 2024)
The article explores the influence of plowing times on agricultural practices, assessing how the timing of plowing impacts soil conditions, seedbed preparation, and ultimately, crop yields. It likely discusses the optimal periods for plowing based on seasonal variations and specific crop requirements. The article delves into the significance of plowing depth as a critical factor in agricultural operations. It likely discusses how different depths of plowing can affect soil structure, nutrient distribution, and water retention, emphasizing the importance of selecting appropriate plowing depths for specific crops and soil types.